Effectiveness of an exercise programme on physical function in patients discharged from hospital following critical illness: a randomised controlled trial (the REVIVE trial). Issue 7 (15th November 2016) - McDowell, Kathryn; O'Neill, Brenda; Blackwood, Bronagh; Clarke, Chris; Gardner, Evie; Johnston, Paul; Kelly, Michaeline; McCaffrey, John; Mullan, Brian; Murphy, Sally; Trinder, T John; Lavery, Gavin; et al.
Abstract : Objective: To investigate the effectiveness of a 6-week exercise programme in patients discharged home following critical illness compared with standard care. Design: Multicentre prospective phase II randomised controlled trial, with blinded outcome assessment after hospital discharge, following the 6-week intervention and at 6 months. Participants: 60 patients (30 per group) aged ≥18 years, mechanically ventilated >96 hours, and not in other rehabilitation, that is, cardiac or pulmonary rehabilitation programmes. Participants in the intervention group completed an individually tailored (personalised) exercise programme. Outcome measures: Primary outcome measure was SF-36 physical functioning following the intervention. Secondary outcomes included a range of performance-based and patient-reported measures. Results: Improvements in the primary outcome did not differ significantly between groups (mean difference (95% CI) 3.0 (−2.2 to 8.2), p=0.26). The intervention group showed significant improvement compared with the control group (mean difference (95% CI)) in SF-36 role physical (6.6 (0.73 to 12.5), p=0.03); incremental shuttle walk test (83.1 m (8.3 to 157.9), p=0.03); functional limitations profile (−4.8 (−8.7 to −0.9), p=0.02); self-efficacy to exercise (2.2 (0.8 to 3.7), p=0.01) and readiness to exercise (1.3 (0.8 to 1.9), p<0.001). These improvements were not sustained at 6 months except readiness to exercise. Improvements in all other secondary outcome measures were not significant. Conclusions: There was no statistically significant difference in the primary outcome measure of self-reported physical function following this 6-week exercise programme. Secondary outcome results will help inform future studies. Trial registration number: NCT01463579. (results), https://clinicaltrials.gov/